SEED-DIPPING APPLICATION OF LOCAL ENDOPHYTIC BACTERIAL CONSORTIUM AGAINST BACTERIAL LEAF BLIGHT OF RICE - Suryadi, Y.; Susilowati, D. N.; Kadir, T. S.; Ruskandar, A. (JURNAL AGROTROPIKA, 2012)
Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae is one of the most important diseases of rice, and to date no effective control measure yet. Alternative controls by several antagonistic microbes have been used to suppress bacterial infection. The aim of this re-search was to investigate antimicrobial effect of bacterial consortium as the primary step to control bacterial blight of rice. A total of five endophytic bacterial consortiums as biocontrol agents were developed and further evaluated for their capability in reducing bacterial blight of rice under screen house condition. The bacterial consortium was applied by seed dipping method using bacterial suspension prior to transplanting. The result showed that bacterial consortia were able to inhibit bacterial blight disease development both in vitro and in vivo test. Consortium labeled as C 1 (containing isolates *E 64,*E 65,*E 66, *C 1A, *C 29D) and C 2 (con-taining isolates *E 64,*E 65,*E 76, *C 1A, *CPKKP 3.5) showed higher bacterial blight percent reduction by two seed-dipping treatments of 24 h and 48 h incubation time, whilst C 4 and C 5 only effective by seed-dipping of 72 h incubation; however none of these consortium affected plant height as well as yield. It was indicated that C 1 and C 2 consortium have relatively high antagonistic activity than that of control treatment and could be applied further to reduce bacterial blight disease development on rice. Key words: Xanthomonas oryzae pv. oryzae, endophytic, rice, bacterial consortium, seed-dipping application